Enhancing Unit-linked Insurance Consumer Loyalty: The Role of Service Quality, Information Asymmetry, and Agent Marketing Strategies - Prasetyo, Edi Yoga; Sumarwan, Ujang; Hasanah, Nur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Unit-linked insurance (PAYDI), Indonesia's top-selling life insurance product, has driven industrial growth in the last two decades through effective agent marketing. However, its complexity, blending protection, and investment have drawn criticism for consumers’ detriment and increasing complaints about insurance agent practices. This study aimed to achieve critical objectives by examining consumer perceptions of agent-provided service quality and distinguishing between active and lapsed policyholders as a measure of loyalty. It also seeks to construct a model that delineates the impact of service quality on consumer satisfaction and loyalty with information asymmetry as a moderating variable. This study used a cross-sectional research design, and gathered data through electronic questionnaires distributed to PAYDI insurance consumers. Purposive sampling was used to select participants, resulting in 159 respondents meeting the study’s criteria. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). These findings underscore the critical influence of agent reliability and empathy on consumer satisfaction with information asymmetry emerging as a key moderator between satisfaction and loyalty. These results imply that reinforcing agent training in reliability, empathy, and efforts to minimize information asymmetry significantly enhances consumer satisfaction and loyalty in the insurance sector. This research suggests that companies should develop a Key Performance Indicator (KPI) and incentives for agents to enhance both customer acquisition and post-purchase services, ensure transparent information sharing, and set measurable satisfaction targets such as the Net Promoter Score (NPS). Future studies should focus on operational diversity and alternative proxies of firms.